Analisis Kesulitan Belajar Peserta Didik Terhadap Materi Matematika, Khususnya Dalam Perkalian Berbentuk Cerita Di Kelas II Sekolah Dasar - Elizabeth Agnesia Manik; Yeri Lestari Gulo; Adrias Adrias; Nur Azmi Alwi (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Students who have difficulty learning mathematics will often make mistakes in learning to count and mistakes in solving word problems in mathematics. The difficulties experienced by students are difficulty in working on story problems due to the inability to understand the meaning of the questions and confusion when determining what arithmetic operations will be used to solve the story problems. The purpose of this research was to analyze the learning difficulties experienced by students as well as the factors that caused students’ learning difficulties in working on multiplication questions in the form of stories in class II elementary school. The method used in this research is descriptive case study. The subjects of this research are students and teachers of class II A at SDN 15 ULU GADUT. The data collection procedures used in the research are test’s, interviews, observation and documentation. The results of the research show that difficulties in learning mathematics include: 1) Difficulty in distinguishing multiplication problems from other material, 2) Student’s writing cannot be read, 3) Difficulty doing calculations in solving multiplication problems. Internal factors include: 1) Lack of enthusiasm for studying, 2) Low numeracy skills and difficulty understanding questions, 3) Not focusing on studying. External factors include: 1) Lack of attention from parents, 2) Often asking students to memorize multiplication, 3) Not using interesting learning media in teaching.